In-situ assembled composite double-layer sulfide solid electrolyte and preparation method thereof
Patent Information
- Application Number
- CN202610798113.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]本发明的目的在于针对现有技术中双层硫化物固态电解质层间结合不紧密、微观结构无序、正负极界面兼容性差,以及非原位复合工艺易出现相分离、离子传输阻抗高的技术缺陷,本发明提供一种原位组装复合双层硫化物固态电解质及其制备方法,通过原位组装与原位复合协同工艺,实现电解质微观结构有序化和层间一体化结合,同时通过分层功能设计,分别适配正负极界面需求,从根本上解决现有技术的核心瓶颈,提升全固态电池的循环稳定性、安全性和离子传导效率
[0030]1.本发明通过原位共价键合实现亲正极功能层与亲负极功能层的一体化结合,无明显相界面,解决了物理堆叠双层电解质层间结合松散、界面阻抗高的缺陷,提升了电解质的结构稳定性。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid-state battery technology, specifically relating to an in-situ assembled composite bilayer sulfide solid electrolyte and its preparation method, and more particularly to a sulfide solid electrolyte and its preparation method that is synergistically constructed through in-situ assembly and in-situ composite, and is layered to adapt to positive and negative electrodes. Background Technology
[0002] Sulfide solid electrolytes are core materials in the field of all-solid-state batteries due to their excellent room-temperature ionic conductivity and good machinability. However, existing sulfide solid electrolytes have significant interface bottlenecks in practical applications: on the one hand, they are prone to oxidative decomposition when in contact with cathode materials, forming a high-resistivity interface layer; on the other hand, they have poor compatibility with lithium metal anodes, easily initiating side reactions and inducing lithium dendrite growth, which seriously affects the cycle stability and safety of all-solid-state batteries.
[0003] To address the aforementioned interface issues, existing technologies often employ physical stacking to prepare bilayer electrolytes, using different functional layers to suit the needs of both positive and negative electrodes. However, this approach suffers from drawbacks such as weak interlayer bonding, poor interfacial contact, and disordered microstructure, resulting in high ion transport impedance and failing to fully leverage the performance advantages of sulfide electrolytes. Furthermore, traditional composite processes often involve non-in-situ mixing, which easily leads to phase separation, further limiting the overall performance and industrial applications of the electrolyte.
[0004] Chinese patent application publication number CN114824457A discloses a high-performance sulfide all-solid-state battery based on a lithium silicon alloy anode with a double-layer electrolyte. Its double-layer structure is usually a simple physical stacking (such as sequential powder laying and pressing), with only physical contact between the layers. It also has defects such as weak interlayer bonding, poor interface contact, and disordered microstructure, resulting in high ion transport impedance and failing to fully utilize the performance advantages of the sulfide electrolyte. Summary of the Invention
[0005] The purpose of this invention is to address the technical shortcomings of existing bilayer sulfide solid electrolytes, such as weak interlayer bonding, disordered microstructure, poor compatibility between positive and negative electrode interfaces, and the tendency for phase separation and high ion transport impedance in non-in-situ composite processes. This invention provides an in-situ assembled composite bilayer sulfide solid electrolyte and its preparation method. Through a synergistic process of in-situ assembly and in-situ composite, the electrolyte achieves ordered microstructure and integrated interlayer bonding. At the same time, through layered functional design, it adapts to the needs of the positive and negative electrode interfaces, fundamentally solving the core bottlenecks of existing technologies and improving the cycle stability, safety, and ion conduction efficiency of all-solid-state batteries.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] The in-situ assembled composite bilayer sulfide solid electrolyte of the present invention is formed by in-situ covalent bonding of a positive electrode functional layer and a negative electrode functional layer to form an integrated bilayer structure. The positive electrode functional layer and the negative electrode functional layer are seamlessly combined through in-situ co-assembly and interfacial covalent cross-linking, with no obvious phase interface, effectively avoiding interlayer peeling and phase separation problems, and improving the overall structural stability of the electrolyte and the continuity of ion transport.
[0008] in:
[0009] The positive electrode functional layer is an oxidation-stabilized sulfide-based composite electrolyte with micro-ordered continuous ion conduction channels inside, which can effectively improve the interfacial compatibility with the positive electrode material.
[0010] The positive electrode functional layer includes a crystalline sulfide fast ion conductor and an in-situ generated positive electrode interface stabilizing component, wherein the positive electrode interface stabilizing component can be uniformly coated on the surface of the crystalline sulfide fast ion conductor.
[0011] The negative electrode functional layer is a reduction-stable sulfide-based composite electrolyte with a gradient-ordered ion conduction network inside, exhibiting excellent reduction stability and lithium affinity.
[0012] The anode-loving functional layer comprises amorphous or low-morpholine sulfides and in-situ polymerized flexible ion-conducting polymers. The flexible ion-conducting polymers and amorphous or low-morpholine sulfides form an interpenetrating network structure, which not only improves the structural flexibility of the anode-loving functional layer to adapt to the volume deformation of the lithium metal anode, but also further optimizes the ion conduction efficiency.
[0013] Preferably, the micro-ordered continuous ion conduction channels are oriented perpendicular to the electrode surface, which can shorten the lithium ion transport path to the greatest extent, reduce the impedance during the transport process, and improve the ion conduction efficiency.
[0014] The gradient-ordered ion conduction network is distributed from the interface between the positive and negative electrode functional layers towards the negative electrode side, further optimizing the continuity of lithium ion transport between the two electrodes, while taking into account both interface stability and conduction efficiency.
[0015] The second objective of this invention is to provide a method for preparing the above-mentioned adaptable in-situ assembled composite bilayer sulfide solid electrolyte. This method employs a synergistic process of in-situ assembly and in-situ composite, which can simultaneously achieve ordered arrangement of precursors, in-situ generation of interfacial stabilizing components, in-situ polymerization of polymers, and interlayer covalent crosslinking. Specifically, it includes the following steps:
[0016] (1) Oriented assembly of positive electrode precursor in an external field to form an ordered precursor film;
[0017] The external field directional assembly is preferably induced by a DC electric field or an alternating magnetic field, with the magnetic field induction intensity being 0.5T~5T. The external field drives the crystalline sulfide fast ion conductor particles in the positive electrode precursor to oriented and align, constructing a primary ordered structure. All steps are carried out under an inert atmosphere, preferably high-purity argon, with oxygen and moisture content in the environment both below 1ppm, laying the foundation for the subsequent formation of micro-ordered ion conduction channels.
[0018] The positive electrode precursor comprises a crystalline sulfide fast ion conductor, a positive electrode interface stabilizing component precursor, and an ion conduction aid.
[0019] (2) Coating the surface of the ordered precursor film with a negative electrode-loving precursor ensures that the two precursor films are in close contact without gaps, providing good conditions for in-situ covalent crosslinking between layers.
[0020] The anode-loving precursor comprises amorphous or hypomorphic sulfides, polymer monomers, lithiophilic components, and an initiator.
[0021] (3) In-situ reaction is carried out, preferably using a segmented programmed heating method. Through precise control of different temperature segments, three key reactions are achieved simultaneously:
[0022] First, the positive electrode interface stabilizing component in the positive electrode precursor reacts in situ to generate nanoscale interface stabilizing components and uniformly coat the surface of crystalline sulfide fast ion conductor.
[0023] Second, the polymer monomers in the anode-loving precursor are polymerized in situ, forming an interpenetrating network structure with amorphous or low-crystalline sulfides; third, the interface between the cathode-loving functional layer and the anode-loving functional layer undergoes an in situ covalent cross-linking reaction, forming a seamless integrated structure.
[0024] (4) The membrane after the reaction is densified to remove residual pores and impurities in the membrane, further improving the density and structural stability of the electrolyte, and finally obtaining a micro-ordered, seamlessly bonded double-layer sulfide solid electrolyte.
[0025] Furthermore, the external field strength in step (1) above is 100V / cm~1000V / cm (electric field) or 0.5T~5T (magnetic field).
[0026] Furthermore, the segmented heating process in step (3) above is as follows: first, heat at 40℃~80℃ for 1~4 hours to initiate the polymerization reaction, and then heat to 100℃~180℃ for 2~6 hours to initiate the crosslinking and crystallization reaction.
[0027] Furthermore, the densification treatment pressure in step (4) above is 10MPa~500MPa.
[0028] The above-mentioned in-situ assembled composite bilayer sulfide solid electrolyte is used in all-solid-state lithium batteries, solid-state lithium-sulfur batteries, or solid-state sodium-ion batteries.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. This invention achieves the integrated bonding of the positive electrode functional layer and the negative electrode functional layer through in-situ covalent bonding, without obvious phase interface, which solves the defects of loose bonding and high interfacial impedance between physically stacked double-layer electrolytes, and improves the structural stability of the electrolyte.
[0031] 2. The layered functional design precisely adapts to the needs of positive and negative electrodes. The oxidation stability and micro-ordered conduction channels of the positive electrode-friendly functional layer effectively suppress the oxidation and decomposition of the positive electrode interface; the reduction stability and gradient ordered conduction network of the negative electrode-friendly functional layer can suppress lithium dendrite growth and significantly improve interface compatibility.
[0032] 3. The in-situ assembly and in-situ composite synergistic process realizes the ordered microstructure of the electrolyte, shortens the lithium-ion transport path, improves ion conduction efficiency, avoids phase separation problems, and optimizes the overall performance of the electrolyte.
[0033] 4. The preparation process is simple and controllable, requires no complex equipment, can achieve large-scale production, has good compatibility with existing all-solid-state battery preparation processes, and has broad application prospects.
[0034] 5. This invention uses a strong magnetic field of 0.5T~5T in conjunction with a strictly inert atmosphere (water oxygen <1ppm) for external field assembly, which not only effectively induces the directional arrangement of sulfide particles and constructs a low-impedance ion transport channel, but also eliminates the oxidation and deterioration of electrolyte materials from the source, significantly improving the ionic conductivity and electrochemical stability of the electrolyte. Detailed Implementation
[0035] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments. Various modifications or substitutions can be made by those skilled in the art without departing from the spirit and essence of the present invention, and all such modifications or substitutions should fall within the protection scope of the present invention.
[0036] Example 1: Preparation of an in-situ assembled composite bilayer sulfide solid electrolyte
[0037] 1. Raw material preparation
[0038] Positive precursor: Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3(Sulphur-germanium ore type) powder 85wt%, positive electrode interface stabilizer precursor (La(NO3) 310wt), conductive additive (graphene) 5wt%.
[0039] The negative electrode precursor is composed of 70wt% amorphous 70Li2S·30P2S5 glass powder, 25wt% polyethylene oxide (PEO, Mw≈106Mw≈106) monomer, 3wt% initiator (diisopropylbenzene peroxide), and 2wt% lithium-loving additive (LiNO3).
[0040] 2. Preparation steps
[0041] (1) Oriented assembly in the field: Under a high-purity argon inert atmosphere (oxygen and moisture content are both less than 1 ppm), the positive electrode precursor is mixed evenly and coated onto the current collector, and placed in a DC electric field (voltage 300 V / cm, time 2 hours) to form an ordered precursor film with an orientation degree of 85%.
[0042] (2) Coating: The negative electrode precursor slurry is uniformly coated on the surface of the ordered film, and the thickness ratio (positive electrode layer: negative electrode layer) is controlled to be 1:3.
[0043] (3) In-situ reaction: The membrane is placed in a vacuum drying oven and first kept at 60°C for 2 hours to initiate in-situ polymerization of PEO. Then, the temperature is raised to 150°C and kept for 4 hours to simultaneously achieve the generation of interfacial stable components and interlayer covalent crosslinking.
[0044] (4) Densification: Hot pressing at 180℃ and 100MPa pressure for 10 minutes, followed by natural cooling and peeling to obtain an integrated double-layer electrolyte membrane.
[0045] Example 2,
[0046] Preparation steps
[0047] (1) Oriented assembly in an external field: The positive electrode precursor is mixed evenly and coated onto an aluminum foil current collector. It is then placed in an alternating magnetic field (magnetic field strength of 0.5T) for 2 hours to form an ordered precursor film with an orientation degree of 85%. The entire operation is carried out in a glove box with a high-purity argon inert atmosphere (water and oxygen content <1ppm).
[0048] (2) Coating: The negative electrode precursor slurry is uniformly coated on the surface of the ordered film, and the thickness ratio (positive electrode layer: negative electrode layer) is controlled to be 1:1.
[0049] (3) In-situ reaction: The membrane is placed in a vacuum drying oven and first kept at 40°C for 4 hours to initiate in-situ polymerization of PEO. Then, the temperature is raised to 100°C and kept for 6 hours to simultaneously achieve the generation of interfacial stable components and interlayer covalent crosslinking.
[0050] (4) Densification: Hot pressing at 180℃ and 10MPa pressure for 10 minutes, then peeling after natural cooling, to obtain an integrated double-layer electrolyte membrane.
[0051] Example 3,
[0052] Preparation steps
[0053] (1) Oriented assembly in an external field: After the positive electrode precursor is mixed evenly, it is coated on an aluminum foil current collector and placed in an alternating magnetic field (magnetic field strength is 5T) for 2 hours to form an ordered precursor film with an orientation degree of 85%. The entire operation is carried out in a glove box with a high purity argon inert atmosphere (water and oxygen content <1ppm).
[0054] (2) Coating: The negative electrode precursor slurry is uniformly coated on the surface of the ordered film, and the thickness ratio (positive electrode layer: negative electrode layer) is controlled to be 1:10.
[0055] (3) In-situ reaction: The membrane is placed in a vacuum drying oven and first kept at 80°C for 2 hours to initiate in-situ polymerization of PEO. Then, the temperature is raised to 180°C and kept for 2 hours to simultaneously achieve the generation of interfacial stable components and interlayer covalent crosslinking.
[0056] (4) Densification: Hot pressing at 180℃ and 500MPa pressure for 10 minutes, followed by natural cooling and peeling to obtain an integrated double-layer electrolyte membrane.
[0057] Example 4: Performance Testing
[0058] The bilayer electrolytes prepared above were assembled into symmetric cells (Li|bilayer electrolyte|Li) and full cells (NCM811|bilayer electrolyte|Li).
[0059] Ionic conductivity: 3.5 × 10⁻⁶ at room temperature −3 S / cm3.5×10 −3 S / cm. Critical current density (CCD): 2.5 mA / cm² (compared to only 1.2 mA / cm² for those fabricated by conventional stacking methods).
[0060] Full battery cycle: After 500 cycles at 0.5C, the capacity retention rate is still 88.5%.
[0061] Comparative Example 1: Physically Stacked Bilayer Electrolytes
[0062] Using the same material, but without applying an electric field or performing segmented in-situ reactions, the two layers of powder are simply physically pressed together.
[0063] Performance Comparison Table
[0064] Performance indicators Example (of the present invention) Comparative Example 1 (Physical Stacking) Improvement effect interlayer bond strength Seamless bonding, crack-free The interface is clear and easy to peel off. Structural stability significantly improved <![CDATA[Interfacial impedance (Ω⋅cm 2 Ω⋅cm 2 )]]> 15.2 85.6 Impedance reduced by approximately 82%. Critical current density (mA / cm²) 2.5 1.2 Double the ability to suppress dendrites
[0065] The electrolyte prepared in this embodiment has tight interlayer bonding, an ordered microstructure, excellent compatibility with the positive and negative electrode interfaces, can effectively suppress interfacial side reactions and lithium dendrite growth, and has high ion conduction efficiency.
[0066] The above description is merely a specific embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, any improvements to the present invention, equivalent substitutions of raw materials, addition of auxiliary components, selection of specific implementation methods, etc., all fall within the protection scope of the present invention.
Claims
1. An in-situ assembled composite bilayer sulfide solid electrolyte, characterized in that, The solid electrolyte is an integrated bilayer structure formed by in-situ chemical bonding of a positive-affin functional layer and a negative-affin functional layer; the positive-affin functional layer and the negative-affin functional layer are seamlessly combined through in-situ co-assembly and interfacial cross-linking, with no obvious phase interface; the positive-affin functional layer has micro-ordered continuous ion conduction channels inside, and the negative-affin functional layer has a gradient-ordered ion conduction network inside.
2. The in-situ assembled composite bilayer sulfide solid electrolyte according to claim 1, characterized in that, The positive electrode functional layer includes a crystalline sulfide fast ion conductor and an in-situ generated positive electrode interface stabilizing component; The crystalline sulfide fast ion conductor is selected from silver-germanium sulfide, lithium-lanthanum-zirconium-titanium oxide-sulfide complex, or Li 10 GeP2S 12 At least one of the (LGPS) type structural sulfides.
3. The in-situ assembled composite bilayer sulfide solid electrolyte according to claim 1, characterized in that, The anode-loving functional layer comprises an amorphous sulfide and an in-situ polymerized flexible ion-conducting polymer; the amorphous sulfide is selected from the Li2S−P2S5 system, the Li2S−SiS2 system, or the LiBH4-based sulfide; the flexible ion-conducting polymer comprises polyethylene oxide (PEO), polypropylene carbonate (PPC), or polyvinylidene fluoride (PVDF) derivatives.
4. The in-situ assembled composite bilayer sulfide solid electrolyte according to claim 1, characterized in that, The micro-ordered continuous ion conduction channels are oriented perpendicular to the electrode surface, and the degree of orientation of the oriented arrangement is greater than 80%.
5. The in-situ assembled composite bilayer sulfide solid electrolyte according to claim 1, characterized in that, The thickness ratio of the positive electrode functional layer to the negative electrode functional layer is 1:1 to 1:
10.
6. A method for preparing an in-situ assembled composite bilayer sulfide solid electrolyte as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) External field orientation assembly: Under an inert atmosphere, a DC electric field or an alternating magnetic field is applied to the positive electrode precursor to induce the oriented arrangement of crystalline sulfide particles and form an ordered precursor film; (2) Coating: Coating the surface of the ordered precursor film with a negative electrode precursor slurry; (3) In-situ reaction: The segmented temperature program is used to simultaneously achieve in-situ coating of the stable components at the cathode interface, in-situ polymerization of polymer monomers and interlayer chemical bonding; (4) Densification: The membrane after reaction is subjected to hot or cold pressing to obtain a dense electrolyte.
7. The preparation method according to claim 6, characterized in that, The external field strength in step (1) is 100V / cm~1000V / cm (electric field) or 0.5T~5T (magnetic field).
8. The preparation method according to claim 6, characterized in that, The segmented temperature rise in step (3) is as follows: first, keep the temperature at 40℃~80℃ for 1~4 hours to initiate the polymerization reaction, and then raise the temperature to 100℃~180℃ and keep it at 2~6 hours to initiate the crosslinking and crystallization reaction.
9. The preparation method according to claim 6, characterized in that, The densification pressure in step (4) is 10MPa~500MPa.
10. The application of the in-situ assembled composite bilayer sulfide solid electrolyte according to any one of claims 1-5 in all-solid-state lithium batteries, solid-state lithium-sulfur batteries or solid-state sodium-ion batteries.
Citation Information
Patent Citations
High-performance sulfide all-solid-state battery with double-layer electrolyte based on lithium-silicon alloy negative electrode
CN114824457A